The evangelizing practice in communities with the face of Jesus - Oro, Ivo Pedro (2024)
Every religious tradition has its collective and communal cultural and experiential expression. Christians have learned from Israel's heritage the importance of being and living as God's people and have experienced, with Jesus and the apostles, being community, sharing life, gifts and goods. The context today is, to a certain extent, of exaggerated individualism, of prioritizing one's own interests and closing oneself off from others. In a frequent expression of Pope Francis, it is building more walls and making fewer bridges (FT 27). The Church urgently needs to return to the ecclesiological key of Vatican II: the Church (all the baptized) is the people of God and the priority that the Latin American episcopate established, especially in Medellín, Puebla and Aparecida, is to live life in communities. Their mission is to humanize and liberate, living out love, mercy and care of life, both internally and by contributing to the building of the Kingdom, transforming society. In the world, the Christian community seeks to be and live as the face and presence of Jesus. This is possible as long as there is a real process of formation, of animators and of Christians in general, in the light of ecclesial and biblical teachings that point us towards the commitment to the Kingdom in the world. It is within this ecclesial scenario, based on a bibliographical approach, that this text aims to contemplate three crucial aspects of Christian mission. The first presents some biblical and ecclesial foundations of community life, which is essential for Christians. The second section looks at aspects of community life that can effectively be a continuing presence of Jesus. In the third section, the aim is to emphasize that the community has a mission in society, because it exists to transform the world into a Kingdom, and not to take refuge in spiritualism or intimism, keeping its back to the problems of human beings and of the life of humanity.